(untitled) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2023)
The information system allows society to be connected to each other without knowing the boundaries of the region with a fast time and is often wrong in its usage. For example, with the utilization of information system makes it very easy for someone’s personal data to be collected and transferred from one party to another without the knowledge of the data owner. Protection of personal data is included in the protection of human rights. Violations of public data abuse in te elections often occur during the registration and verification of election participants. At this case, public data is widely used to smooth the way for candidates for political parties and candidates for the Regional Representatives Council (DPD) so they can be declared as election participants. Many society do not know that their personal data is retrieve to qualify for political party membership and the minimum support requirements for DPD voters. This conditions is feared will continue without any movement to change patterns so that each party can know the dangers of retrieve personal data. The type of research used by the author in analyzing the problems of this research is using normative research types and using secondary data sources as well as statutory approaches, case approaches, and contextual approaches.